Pelatihan Terpadu SDM Perangkat Gampong dalam Pengembangan BUMG Kulam Jaya di Meureudu Kab. Pidie Jaya - Kamaruddin, Kamaruddin; Azhari, Azhari; Hasbi, Hasbi; Konadi, Win; Musrizal, Musrizal; M. Ikhsan Mangkuwinata, Sonny (Aceh Journal of Community Engagement (AJCE), 2024)
The problem of human resource performance, especially village/gampong apparatus in developing BUMG, is still considered not optimal and efficient, this is evident from the BUMG Meunasah Kulam business unit program in Meureudu District, Pidie Jaya Regency since its establishment in 2022 until now, the benefits have not been felt as expected. This is directly and indirectly related to the ability of the human resources of the perpetrators. BUMG Meunasah Kulam, Meurudu District, Pidie Jaya Regency was established in order to develop and empower the economy of village/gampong communities. However, the problems related to BUMG are that they have not fully synergized in developing village potential and have not supported the sustainability of community economic empowerment. Therefore, Pengabdi carries out community service to foster human resources for village apparatus who run BUMG so that they have performance, especially in organizing programs, developing BUMG business units and making transparent and accountable financial reports. And make BUMG Meunasah Kulam, Meureudu District, Pidie Jaya Regency able to develop in the future.